The structure of world reporting in Mpu Prapañca’s travels in Kakawin Nāgarakṛtāgama: A study of Carl Thompson’s travel literature - Mamluatun Ni'mah (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2026)
This research addresses the tendency in Kakawin Nāgarakṛtāgama studies to predominantly treat the text as a historiographical and ideological source, overlooking a systematic examination of its travel dimensions and the author's world-reporting methods from a travel literature perspective. The main problem of this research is how Mpu Prapañca reports the world through his travel experiences in Kakawin Nāgarakṛtāgama. This research aims to analyze the structure of world reporting in Mpu Prapañca's travels from the perspective of Carl Thompson's travel literature. This research employs a qualitative, descriptive-analytical approach. The primary research data consist of the Kakawin Nāgarakṛtāgama text itself, which describes the journey, supplemented by supporting data from interviews with experts in Old Javanese literature, textual observation, and library documentation. Data collection techniques include document studies, reading and note-taking, limited interviews, and literature reviews, while data analysis is conducted through content analysis grounded in the theory of travel literature. The results of the study indicate that the world in Kakawin Nāgarakṛtāgama is systematically structured through a recurring spatial framework, including villages, waters, forests, and mountains, and is conveyed from a near-destination perspective. The conclusion of the study confirms that Kakawin Nāgarakṛtāgama is a pre-modern travel literature text that consciously constructs the world through travel experiences, thus broadening the understanding of classical Nusantara literature within the framework of travel literature theory. This framework can be applied to other classical Nusantara texts containing travel structures for further research.